Critique of pure reason - Kant, Immanuel, 1724-1804.; Meiklejohn, J. M. D. (John Miller Dow), 1836-1902. (Waiheke Island : Floating Press, 2009)
The Critique of Pure Reason is one of the seminal texts of Western philosophy, and the first of Kant's three Critiques. In it he takes up Hume's argument that cause and effect cannot be experienced by the senses. Hume argued that we experience events one after the other, but not that one event is caused by the preceding event. Kant argues that synthetic, rather than analytic thinking is needed, and addresses the problem of thinking synthetically without relying on the empirical ...
Title; Contents; Preface to the First Edition, 1781; Preface to the Second Edition, 1787; Introduction; I TRANSCENDENTAL DOCTRINE OF ELEMENTS; First Part Transcendental Aesthetic; Second Part Transcendental Logic; Transcendental Logic First Division; Book I; Book II; Transcendental Logic Second Division; Book I Of the Conceptions of Pure Reason; Book II Of the Dialectical Procedure of Pure Reason; II TRANSCENDENTAL DOCTRINE OF METHOD; Endnotes
eBooks on EBSCOhost
Keywords: Knowledge, Theory of -- Early works to 1800.; Causation -- Early works to 1800.; Reason -- Early works to 1800.; Théorie de la connaissance -- Ouvrages avant 1800.; Raison -- Ouvrages avant 1800.; PHILOSOPHY -- History & Surveys -- Modern; Causation; Knowledge, Theory of; Reason; Electronic books; Electronic books; Early works